IMPLEMENTASI KURIKULUM MERDEKA DENGAN MEMANFAATKAN SUMBER DAYA ALAM UNTUK MENINGKATKAN KEMANDIRIAN DAN KREATIVITAS - Purwiyanti, Purwiyanti; Sujatmiko, Riyadi; Restari, Trismayanti Endang; Dharmawan, Azhari; Putri, Fadhilah Nur Islami Melinia; Ramadhan, Tio; Pardede, Rita Sariana; Sihombing, Erni; Ikhsanudin, Ikhsanudin; Rezeki, Yanti Sri (STKIP Persada Khatulistiwa Sintang, 2023)
ABSTRACT The village of Punggur is one of the villages with a relatively low level of education, where only 5% of its population pursue higher education and only 0.15% of them manage to complete high school. In an effort to address the low education level in Punggur Village, a small Village is home to a Community Learning Center (PKBM) named